If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + -2a + 5 = 0 Reorder the terms: 5 + a + -2a = 0 Combine like terms: a + -2a = -1a 5 + -1a = 0 Solving 5 + -1a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1a = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1a = 0 + -5 -1a = 0 + -5 Combine like terms: 0 + -5 = -5 -1a = -5 Divide each side by '-1'. a = 5 Simplifying a = 5
| -5(17)+y=13 | | (x^2)-((x^3)/6) | | 4/5x-7x=6 | | 7x(x-3)(x+2)=0 | | 12x+3y=162 | | X/8+2=14 | | m+10-14m=-5 | | (3-3/2y)^2 | | -3x+3(5+13)=3 | | x-3+5x= | | 4k-28k=-49 | | 7x-4/5x=6 | | H/5+3=-6 | | 11(4-6x)+5(13y+1)=9 | | 3x+7-5x= | | 4k-14+3/c=21 | | 5h=2 | | 0=2m-18 | | -0.3f+1.3=4.8 | | -18/y+3 | | (x+16)+(x+22)=231 | | y^2-3y/y+3 | | 5(4x)-1/2x=234 | | 9h+4.5-7h+1.75= | | 6x+3x-3= | | 12+7C=103 | | 21-1y=-87+2y | | 6y-5-2y=-31 | | -2/3n-6=18 | | -7+28m=13(2m-3) | | 2v-54=-1v+21 | | 0.5n+0.3n-0.4n= |